L'approccio integrato in psicoterapia: origini, configurazioni attuali, prospettive formative - Marco Architravo (Marp Edizioni, 2020)
Through a historical recapitulation of how the concept of integration in psychotherapy has evolved over time, in relation to changes in society, it is intended to underline how the current configuration can find a further development according to the complexity of the present time. In particular, the focus is centered on the experience of the psychotherapist starting from his specialist training, as an element of integration of its clinical practice regardless of the use of techniques and the training reference of common factors.